A VSV-based assay quantifies coronavirus Mpro/3CLpro/Nsp5 main protease activity and chemical inhibition - Emmanuel Heilmann; Francesco Costacurta; Stephan Geley; Seyad Arad Mogadashi; Andre Volland; Bernhard Rupp; Reuben Stewart Harris; Dorothee von Laer (Communications Biology, 2022)
A vesicular stomatitis virus (VSV)-based assay enables high-throughput screening for small molecular protease inhibitors that can block viral proteases, like the Mpro/3CLpro/Nsp5 in SARS-CoV-2.